Elaborasi Metode Pembelajaran Pengenalan Al-Qur’an Berbasis Metode Wafa pada Anak Kelompok A TK Darul Ilmi Jambangan Surabaya - Ahmad Fachrurrazi; Era Yuliani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research was motivated by the researcher's interest in studying the application of the Wafa method in introducing the hijaiyah letters to early childhood at Darul Ilmi Kindergarten. The Wafa method is a learning approach that uses the Quantum Teaching concept with the Tandur pattern, which is an acronym for Tumbuhkan, Alami, Namai, Demonstrate, Ulangi, and Celebrate. This pattern is designed to meet the needs of introducing the hijaiyah letters to early childhood. The purpose of this study was to determine how the Wafa method is applied in introducing the hijaiyah letters to early childhood at Darul Ilmi Kindergarten. The main focus examined in this research is (1) how is the Wafa method implemented in Darul Ilmi Kindergarten? This research uses a qualitative approach with a descriptive type. The data collection techniques used were observation, interviews and documentation. Meanwhile, the data analysis techniques applied include data reduction, data presentation and verification. The results of the research show that: the application of the Wafa method in Darul Ilmi Kindergarten refers to activities that have been prepared by the Wafa Center and the introduction of hijaiyah letters using the Wafa method helps young children recognize hijaiyah letters which are in accordance with their makhraj and tajwid. This shows that the Wafa method makes it easier for children to recognize hijaiyah letters, as seen from learning activities, the teacher's activeness in teaching, and the learning results obtained.